(untitled) (Research, Society and Development, 2022)
The purpose of the study is to highlight the importance of cooperation between Higher Education Institutions and Companies, especially small and micro-sized ones, for the insertion of these companies in the so-called world of the fourth industrial revolution, with the help of researchers from the stricto sense, through the practical application of the concepts of Industry 4.0, thus promoting the dissemination of knowledge as well as breaking possible paradigms that may exist, thus raising the level of these organizations in an increasingly competitive market since the technological process becomes irreversible. and constant. In addition to the proposed conceptual synthesis, the article establishes a theoretical framework for such implementation, making its implementation possible. The proposed model for the inclusion of academics and organizations in the authors’ view becomes a starting point where there is still much to be developed and to be increased, and this is one of the objectives of this discussion, to foster ideas about the importance of this theme.